2021
DOI: 10.47923/2021.14000
|View full text |Cite
|
Sign up to set email alerts
|

"Advanced" isn't Always Better: Assessing the Safety, Security, and Environmental Impacts of Non-Light-Water Nuclear Reactors

Abstract: The Union of Concerned Scientists puts rigorous, independent science to work to solve our planet's most pressing problems. Joining with people across the country, we combine technical analysis and effective advocacy to create innovative, practical solutions for a healthy, safe, and sustainable future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The latter category encompasses early nuclear power technologies such as fast breeder reactors, molten salt reactors, and high-temperature reactor concepts. However, non-conventional reactor concepts, including those promoted by the "Generation IV International Forum" (GIF), are still several decades away from potential commercial deployment, if they ever become viable, and are unlikely to achieve competitive status in the near future (Cochran et al, 2010;Lyman, 2021;Pistner et al, 2023;Böse et al, 2024). A summary of the issues at stake is provided by Wimmers et al (2023).…”
Section: Small Modular Reactors and Non-conventional Reactor Concepts...mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter category encompasses early nuclear power technologies such as fast breeder reactors, molten salt reactors, and high-temperature reactor concepts. However, non-conventional reactor concepts, including those promoted by the "Generation IV International Forum" (GIF), are still several decades away from potential commercial deployment, if they ever become viable, and are unlikely to achieve competitive status in the near future (Cochran et al, 2010;Lyman, 2021;Pistner et al, 2023;Böse et al, 2024). A summary of the issues at stake is provided by Wimmers et al (2023).…”
Section: Small Modular Reactors and Non-conventional Reactor Concepts...mentioning
confidence: 99%
“…experience with safety regulation (Ramana et al, 2013;Yamashita, 2015). Also, a large number of reactors with low capacities implies significant proliferation risks of the fissile material (Glaser et al, 2013;Lyman, 2013). According to a recent survey conducted by Thomas and Ramana (2022), it is revealed that even reactor designs based on thoroughly tested technology cannot be implemented before the year 2030.…”
Section: Iaea (mentioning
confidence: 99%